Dynamics of Culture and Media Power: Analysis of Misogyny in Online News in Indonesia - Susanti, Vinita; Rosyidah, Ida; Sahetapy, Elfina Lebrine (Jurnal Ilmu Sosial Indonesia (JISI), 2024)
Abstract. This article examines the phenomenon of media misogyny occurring in the context of online news in Indonesia. A survey indicates that Indonesian society tends to choose online news as the primary source of information, allowing people to easily contribute to and consume various information. Nevertheless, news media has significant freedom to produce news without strict limitations. The consequence is the potential for the public to become victims of crimes when they are portrayed as subjects in reporting, particularly in relation to the phenomenon of media misogyny. The focus of this research is to explain how media misogyny is manifested in online reporting using a qualitative approach, involving interviews with journalists and editors, as well as an analysis of the resulting news. The theory used in this analysis is Radical Feminism. The research findings show violations of the Journalistic Code of Ethics, gender inequality manifested in the lack of women's participation in the online news production process, and the impact on the production of news that is gender-biased and misogynistic. Keywords: Radical Feminism, Media Misogyny, Gender Inequality, Media Power, Patriarchal Culture. Abstrak. Artikel ini mengkaji fenomena misogini media yang terjadi dalam konteks berita online di Indonesia. Sebuah survei menunjukkan bahwa masyarakat Indonesia cenderung memilih berita online sebagai sumber informasi utama, sehingga masyarakat dapat dengan mudah berkontribusi dan mengonsumsi berbagai informasi. Meski demikian, media berita mempunyai kebebasan yang signifikan untuk menghasilkan berita tanpa batasan yang ketat. Konsekuensinya adalah masyarakat berpotensi menjadi korban kejahatan jika mereka dijadikan sebagai subjek pemberitaan, khususnya terkait dengan fenomena misogini media. Fokus penelitian ini adalah menjelaskan bagaimana misogini media diwujudkan dalam pemberitaan online dengan menggunakan pendekatan kualitatif, yang melibatkan wawancara dengan jurnalis dan redaksi, serta analisis terhadap berita yang dihasilkan. Teori yang digunakan dalam analisis ini adalah Feminisme Radikal. Temuan penelitian menunjukkan adanya pelanggaran terhadap Kode Etik Jurnalistik, ketidaksetaraan gender yang diwujudkan dalam kurangnya partisipasi perempuan dalam proses produksi berita online, dan dampaknya terhadap produksi berita yang bias gender dan misoginis. Kata Kunci: Feminisme Radikal, Misogini Media, Ketimpangan Gender, Kekuatan Media, Budaya Patriarki.